Rediseño interior del Centro de Desarrollo Infantil ``Parvulitos Soñadores´´ basado en el método Montessori para una mejor funcionalidad en la parroquia Santa Rosa-Ambato - Cunalata Altamirano, Brayan Fabricio (2024)
The objective of this degree project is the interior redesign of the Child Development Center ``Parvulitos Soñadores based on the Montessori method for better functionality in the parish of Santa Rosa-Ambato, which presents functional and aesthetic drawbacks. This CDI serves children from 12 to 36 months of age, where the current norms and elements of public organizations that govern these child development centers are examined to create cozy, safe and comfortable environments. With the help of the Montessori method it provides a prepared environment: tidy, simple, aesthetic and real for children and teachers. A complete design proposal is proposed that includes the organization of space, lighting, ventilation, furniture and finishes appropriate for the different activities that are developed within the CDI.